Emergence of pathogenic and multiple‐antibiotic‐resistant Macrococcus caseolyticus in commercial broiler chickens. Issue 6 (25th May 2018) - Li, Gen; Du, Xusheng; Zhou, Defang; Li, Chengui; Huang, Libo; Zheng, Qiankun; Cheng, Ziqiang
Abstract: Macrococcus caseolyticus is generally considered to be a non‐pathogenic bacterium that does not cause human or animal diseases. However, recently, a strain of M. caseolyticus ( SDLY strain) that causes high mortality rates was isolated from commercial broiler chickens in China. The main pathological changes caused by SDLY included caseous exudation in cranial cavities, inflammatory infiltration, haemorrhages and multifocal necrosis in various organs. The whole genome of the SDLY strain was sequenced and was compared with that of the non‐pathogenic JCSC5402 strain of M. caseolyticus . The results showed that the SDLY strain harboured a large quantity of mutations, antibiotic resistance genes and numerous insertions and deletions of virulence genes. In particular, among the inserted genes, there is a cluster of eight connected genes associated with the synthesis of capsular polysaccharide. This cluster encodes a transferase and capsular polysaccharide synthase, promotes the formation of capsules and causes changes in pathogenicity. Electron microscopy revealed a distinct capsule surrounding the SDLY strain. The pathogenicity test showed that the SDLY strain could cause significant clinical symptoms and pathological changes in both SPF chickens and mice. In addition, these clinical symptoms and pathological changes were the same as those observed in field cases. Furthermore, the anti‐microbial susceptibility test demonstrated that the SDLY strain exhibits multiple‐antibiotic resistance. The emergence of pathogenic M. caseolyticus indicates that more attention should be paid to the effects of this micro‐organism on both poultry and public health.